Trends in Life Expectancy of Cystic Fibrosis Patients in Moscow and their Connection with the Treatment Received: Retrospective Analysis for 1993–2013 - N. Yu. Kashirskaya; S. A. Krasovsky; A. V. Chernyak; V. D. Sherman; A. Yu. Voronkova; L. A. Shabalova; V. S. Nikonova; Yu. V. Gorinova; O. I. Simonova; E. L. Amelina; E. I. Kondrat’eva; N. I. Kapranov; et al. (Вопросы современной педиатрии)
Cystic fibrosis is multiple organ pathology that requires a complex treatment. Its standardization and pharmacoeconomic analysis are absolutely necessary. We performed a retrospective analysis of the trends in life expectancy of cystic fibrosis patients who lived inMoscow in 1993, 1998, 2003, 2008, and 2013. It was found that the survival rate of these patients depended on the choice of drug therapy (pancreatic enzymes, dornase alfa, intravenous and inhaled antipseudomonal antibiotics), changes in diet, active dispensary observation at a specialized center for cystic fibrosis, and neonatal screening. We determined the cost of drug therapy per patient. From 1993 to 2013, the survival rate of patients who lived in Moscow increased by more than 20 years (from 16 to 39 years, respectively). The average cost of therapy increased more than 10 times (from USD 1.8 to 21.9 thousand, respectively).